Self-reported on food allergy among university students in Dengkil, Selangor - Tengku Azhar, Tengku Norbaya; Mohd. Idris, Siti Noorfarhana; Abdul Ghani, Radiah; Che Hassan, Muhammad Rahimi; Haridan, Umi Shakina; Mohamed, Malissa; Abd Wahab, Noor Akmal; Mohd. Zazi, Norhafizah (2020)
Prevalence of allergy is a worldwide issue. The outbreak contributes to social and economic burden of the sufferer as well as the society. In Malaysia, the condition has continued to worsen due to the misconception of certain allergy symptom. It also leads to improper clinical diagnosis which affects the accuracy of treatment and upturns the cost further. This circumstances are corresponded to the level of public awareness and knowledge about the terms, symptoms and allergy prevention. This study highlighted the allergy prevalence among young adults based on self–reported approach. This cross-sectional study involved 138 students between the age of 18 to 19 years old from the Centre of Foundation Studies, UiTM Cawangan Selangor, Kampus Dengkil. Overall, the allergy prevalence reported in this study showed higher occurrence compared to previous study of self-reported and clinical data within the same population. The data indicated that n=80 (58%) of respondents indicating seafood such as shrimp as the most common implicated food allergen at n=43 (31.25%) followed by house dust mite at n=40 (29%) and peanuts at n=14 (10.1%). Pearson correlation between respondents’ knowledge of allergy terms, causes and symptoms with allergy prevention and treatment practice shows high significant correlation with (r = 0.387, P<0.001). Chi Square Test among students with allergies who were getting consultation from health personnel showed significant association (P<0.001) in which 41 (59.4%) of students with allergies do not consult any health personnel. As a conclusion, self-reported is only useful to give surface overview on allergy prevalence, but detailed clinical diagnosis is compulsory to ensure the effectiveness of allergy prevention and treatment in the future.